PEMANTAUAN PLANKTON DAN KUALITAS AIR TAMBAK UDANG WINDU INTENSIVE DI LAHAN PASIR PANTAI - Bambang Triyatmo (Jurnal Perikanan Universitas Gadjah Mada, 2003)
A research was conducted in intensive ponds of shrimp (Penaeousmonodon) culture located in sandy coastal area Pandansimo, Bantul Regency. Shrimp was cultured in two ponds (± 3.600 m2 each). The bottom of the first pond was 5-10 cm of soil. The second pond used sand originated from the coastal area as the bottom. Shrimps were cultured in the two ponds for 4.5 months. During the culture, plankton and water quality of ponds was observed for 3 times, namely on early, middle and final of shrimp culture.Result of the experiment indicated that 1). Density of plankton in both increased during shrimps culture; 2). Density of plankton in the pond with soil bottom was higher than in that of the pond with sand bottom; 3). The productivity of ponds increased; 4). As higher plankton density increase the absorption of NH4 and PO4, the availability of these nutrient gradually lowered; 5). Species composition of plankton in ponds with soil bottom was dominated by Spirulina sp. Brachionus sp., and Chlorella sp.; 6) In addition species composition of plankton in ponds with sand bottom was dominated by., Brachionus sp., Chlorella sp., Spirulinasp., and Cyclotella sp.; 7) During shrimp culture, the water qualities of the ponds were commonly in the optimal condotions for shrimp; 8) Water quality for the first three months of culture generally was suitable for shrimp culture both in pond with soil and sand bottom. However, after 90 days of culture, the dissolved oxygen in ponds with soil and sand bottom ranged from 2.0 to 3.0 mg/l, which was unsuitable for shrimp culture; 9) The production, survival rates and average body weights of shrimp were 3.18 ton/ha, 12.23 g and 42.3% from pond with soil bottom, and 3.51 ton/ha, 14.43g and 43.38% from pond with sand bottom, respectively.